2002
DOI: 10.1038/sj.cgt.7700467
|View full text |Cite
|
Sign up to set email alerts
|

Human growth hormone gene transfer into tumor cells may improve cancer chemotherapy

Abstract: Chemotherapy remains the main tool for the treatment of cancers, but is often hampered by tumor cell resistance. In this context, the transfer of genes able to accentuate the effect of anticancer drugs may constitute a useful approach, as exemplified by inactivation of nuclear factor ( NF ) -B via direct transfer of a gene encoding a negative dominant of its natural inhibitor IB, leading to improved response to cancer chemotherapy. Following our previous report that transfection of human growth hormone ( hGH )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The effect of hGH is mediated via a glutathione-dependent decrease in NF-kB translocation normally observed in response to TNF-a. We alsoconfirmed these findings in vivo, as injections of exogenous recombinant hGH in U937 tumour-engrafted nude mice led to increased tumour cell death together with decreased translocation of NF-kB in cell nuclei, in response to subtoxic doses of daunorubicin, an anthracycline agent activating NF-kB in our cells (Cherbonnier et al, 2002).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The effect of hGH is mediated via a glutathione-dependent decrease in NF-kB translocation normally observed in response to TNF-a. We alsoconfirmed these findings in vivo, as injections of exogenous recombinant hGH in U937 tumour-engrafted nude mice led to increased tumour cell death together with decreased translocation of NF-kB in cell nuclei, in response to subtoxic doses of daunorubicin, an anthracycline agent activating NF-kB in our cells (Cherbonnier et al, 2002).…”
supporting
confidence: 67%
“…Moreover, daunorubicin, widely used in clinical practice, is able to induce apoptosis and activate NF-kB in our cells (Cherbonnier et al, 2002). We therefore decided to study the effect of exogenous recombinant hGH on chemotherapy delivered to nude mice engrafted with parental unmodified U937 tumours.…”
Section: In Vivo Sensitisation Of Tumours By Rhghmentioning
confidence: 99%
See 1 more Smart Citation
“…9 By contrast, other studies have failed to demonstrate an effect of GH on cancer development 10 or have concluded that GH may actually improve the efficacy of cancer chemotherapy. 11 Preclinical studies in rodents have suggested that anabolic hormones, such as GH and IGF-I, may reverse the catabolic state associated with cachexia, one of the major complications of cancer and cancer therapies, 12 as well as inhibit metastases in tumor-bearing animals. 13,14 In this study, the use of species-specific GHRH was not necessary.…”
mentioning
confidence: 99%
“…Recent studies have shown an effect of hGH on cell survival by regulating nuclear factor-kappa B activity, leading to apoptosis in leukaemia cell lines. 9 Also, Cherbonnier et al 9,27 showed that hGH-transfected tumour cells engrafted in nude mice responded in vivo to chemotherapy with non-toxic doses of daunorubicin, whereas, under the same conditions, control tumour cells remained insensitive. We show that it is safe to use hGH in this group of patients treated intensively with chemotherapy and/or stem cell transplantation, and that it does not increase relapse rate and improves platelet reconstitution.…”
Section: Discussionmentioning
confidence: 99%